2015
DOI: 10.4103/0973-6131.154075
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of yogic breathing intervention on quality of life of opioid dependent users

Abstract: Introduction:The quality of life (QOL) of substance users is known to be impaired. Sudarshan Kriya Yoga (SKY), a yogic breathing program has potential to improve QOL and needs evaluation in an Indian setting.Aims:Study aimed to assess changes in QOL in treatment seeking male opioid dependent users following practice of SKY program.Settings and Design:Users were randomized into study (n = 55) and control group (n = 29). Study group besides standard treatment (long term pharmacotherapy with buprenorphine in flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 5 publications
1
26
0
1
Order By: Relevance
“…Of the selected studies, 34 were experimental studies with randomized sampling [4,5,8,9,11,12,15,17,18,21,25,27,29,30,46,48,49,52,54,55,[59][60][61][63][64][65][68][69][70][71][74][75][76][77], while the rest were quasi-experimental [6,7,10,13,14,16,20,22,26,28,47,50,51,53,[56][57][58]62,…”
Section: Descriptive Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the selected studies, 34 were experimental studies with randomized sampling [4,5,8,9,11,12,15,17,18,21,25,27,29,30,46,48,49,52,54,55,[59][60][61][63][64][65][68][69][70][71][74][75][76][77], while the rest were quasi-experimental [6,7,10,13,14,16,20,22,26,28,47,50,51,53,[56][57][58]62,…”
Section: Descriptive Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…Aerobic exercise was the most used type of program, finding 27 studies that used this type of exercise [4,5,7,8,[10][11][12][13]16,18,22,26,46,49,50,56,57,[59][60][61]67,[74][75][76][77][78][79]. In addition, 14 studies were found that used exercise programs related to body-mind practices, such as yoga, tai chi or qigong [9,15,21,[28][29][30]54,55,[64][65][66]70,71,73], 10 who used combined strength and aerobic exercise [6,17,20,27,32,47,48,52,68,…”
Section: Descriptive Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a number of substance abuse treatment programs have incorporated yoga or meditation as contributing therapies, and there is some research demonstrating efficacy of such treatments for adults (Carim-Todd et al 2013; Hallgren et al 2014). In addition, a number of studies have evaluated the specific effects of yoga interventions on addictive behavior, substance use risk factors, and substance abuse itself and have found positive results for adults, such as improvements in quality of life in opioid-dependent users (Dhawan et al 2015), reduced risk of alcohol and drug use in women with posttraumatic stress disorder (Reddy et al 2014), improved global functioning and well-being in substance-dependent inpatients (Sureka et al 2014), and improved mood and quality of life in women undergoing heroin detoxification (Zhuang et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Only one study was done in Indian population reported significant increase in physical, psychological, and environmental domains of QoL (WHO-QOL scale) in patient group who also received Sudarshan Kriya Yoga therapy in combination of standard treatment (buprenorphine) as compared to standard treatment alone. [ 24 ]…”
Section: R Esults and Discussionmentioning
confidence: 99%